Notoginsenoside R1 Attenuates H/R Injury in H9c2 Cells by Maintaining Mitochondrial Homeostasis - Yuanbo Xu; Piao Wang; Ting Hu; Ke Ning; Yimin Bao (Current Issues in Molecular Biology)
Mitochondrial homeostasis is crucial for maintaining cellular energy production and preventing oxidative stress, which is essential for overall cellular function and longevity. Mitochondrial damage and dysfunction often occur concomitantly in myocardial ischemia–reperfusion injury (MIRI). Notoginsenoside R1 (NGR1), a unique saponin from the traditional Chinese medicine Panax notoginseng, has been shown to alleviate MIRI in previous studies, though its precise mechanism remains unclear. This study aimed to elucidate the mechanisms of NGR1 in maintaining mitochondrial homeostasis in hypoxia/reoxygenation (H/R) H9c2 cells. The results showed that NGR1 pretreatment effectively increased cell survival rates post-H/R, reduced lactate dehydrogenase (LDH) leakage, and mitigated cell damage. Further investigation into mitochondria revealed that NGR1 alleviated mitochondrial structural damage, improved mitochondrial membrane permeability transition pore (mPTP) persistence, and prevented mitochondrial membrane potential (Δψm) depolarization. Additionally, NGR1 pretreatment enhanced ATP levels, increased the activity of mitochondrial respiratory chain complexes I–V after H/R, and reduced excessive mitochondrial reactive oxygen species (mitoROS) production, thereby protecting mitochondrial function. Further analysis indicated that NGR1 upregulated the expression of mitochondrial biogenesis-related proteins (PGC-1α, Nrf1, Nrf2) and mitochondrial fusion proteins (Opa1, Mfn1, Mfn2), while downregulating mitochondrial fission proteins (Fis1, Drp1) and reducing mitochondrial autophagy (mitophagy) levels, as well as the expression of mitophagy-related proteins (Pink1, Parkin, BNIP3) post-H/R. Therefore, this study showed that NGR1 can maintain mitochondrial homeostasis by regulating mitophagy, mitochondrial fission–fusion dynamics, and mitochondrial biogenesis, thereby alleviating H9c2 cell H/R injury and protecting cardiomyocytes.